Diagnostic value of NT-proBNP in identifying impaired coronary flow reserve in asymptomatic moderate or severe aortic stenosis. (April 2013) - Banovic, Marko; Vujisic-Tesic, Bosiljka; Bojic, Svetlana; Mladenovic, Ana; Ignjatovic, Svetlana; Petrovic, Milan; Trifunovic, Danijela; Nedeljkovic, Ivana; Popovic, Dejana; Callahan, Mark; Seferovic, Petar
Aim: NT-proBNP has been shown to be a reliable biochemical marker for left ventricular wall stress. The relationship between NT-proBNP and coronary flow reserve (CFR) was evaluated in patients with significant asymptomatic aortic stenosis (AS).Methods: A total of 74 patients with moderate or severe AS, mean age 66.68 ± 10.02 years (56.75% males), were enrolled in this prospective study. All patients underwent coronary angiography and had no obstructive coronary disease (defined as having no stenosis >50% in diameter). They had all undergone standard transthoracic Doppler-echo study and adenosine stress transthoracic-echo for CFR measurement and laboratory analysis for NT-proBNP measurement.Results: The median NT-proBNP value was significantly increased (417.0 pg/ml; interquartile range [IQR]: 176.8–962.2 pg/ml). NT-proBNP was significantly higher in the group with CFR ≤2.5 (median: 549.0 pg/ml; IQR: 311.5–1131.0 pg/ml; as opposed to median: 291.5 pg/ml; IQR: 123.0–636.2 pg/ml; W = 452; p = 0.012). NT-proBNP showed significant negative correlation with CFR (ρ = -0.377, p = 0.001). There was also significant correlation between NT-proBNP and E/E´, S´ and aortic valve resistance. The NT-proBNP value of 334.00 pg/ml was determined as the best cut-off value for the diagnosis of CFR ≤2.5 (area under the curve: 0.67; 95%CI: 0.54–0.79; p < 0.01) and the sensitivity and specificity were 74 and 64%, respectively.Conclusion: Elevated NT-proBNP can indicate patients with impaired CFR in asymptomatic moderate or severe AS patients with preserved ejection fraction and nonobstructive coronary arteries.